Ecology and biogeography of myxomycetes - Schnittler, Martin (2001)
Plasmodial slime moulds (Myxomycetes) are a group of protista-like micro-organisms forming small but macroscopic fructifications. The thesis summarizes the results from a series of original papers on the ecology and diversity of Myxomycetes from the Arctic to the Neotropical zone. New microhabitats for these organisms are characterized ecologically, and a general picture about the distribution of myxomycete diversity among the major vegetations zones of the world is presented. Die plasmodialen Schleimpilze (Myxomycetes) sind protistenähnliche Mirkoorganismen, die kleine, aber makroskopische Ausmaße erreichende Fruktifikationen bilden. Die vorliegende Arbeit fasst die Ergebnisse einer Reihe von Originalarbeiten zur Ökologie und Artendiversität von Myxomyceten von der Arktis bis hin zur Neotropis zusammen. Neu entdeckte Mikrohabitate dieser Organismen werden vorgestellt, und ein Bild über die Diversitätsverteilung der Myxomyceten innerhalb der großen Vegetationszonen der Welt wird entworfen.